Pengembangan Modul Pendidikan untuk Meningkatkan Problem Based learning Pada Mata Pelajaran IPAS Kelas V SD - Handayani, Citra Wuri; Nisa, Ana Firotun; Saputra, Bherrio Dwi (Universitas Sarjanawiyata Tamansiswa, 2025)
The issue of low implementation of Problem-Based Learning (PBL) among elementary school students, particularly in Science and Social Studies (IPAS) learning, has become a concern in efforts to enhance problem-solving skills. This study aims to develop a PBL-based educational module that can improve problem-solving skills in Grade V elementary school students. This research is categorized as Research and Development (R&D), with stages including design, expert validation, limited trials, and evaluation. The research subjects consist of two groups: a control group and an experimental group, with the latter being treated using the PBL module. Data collection was conducted through observations, questionnaires, and problem-solving ability tests. Data analysis employed normality tests and parametric statistical tests to determine differences in results between the groups. The findings indicate that the PBL-based educational module is feasible, effective, and practical for enhancing students' problem-solving skills. These results support the research goal, demonstrating that the development of the PBL-based educational module positively influences students' problem-solving abilities. However, several components, such as lesson design and module content, still require further refinement. This research provides an important contribution to the development of an applicable PBL teaching module in IPAS learning, aimed at enhancing critical thinking and problem-solving skills in elementary school students.